Internalization of quality in public organizations. Issue 3 (20th October 2020) - Tarí, Juan José; Molina-Azorín, José F.; Pereira-Moliner, Jorge; López-Gamero, María D.
Abstract : Purpose: This paper examines the relationships between: (1) motives for internalization of a quality system, (2) the internalization of a quality system and (3) customer results, employee results and social results in public organizations by means of replication research Design/methodology/approach: First, the work applies a quantitative study to test hypotheses using structural equations based on the Partial Least Squares (PLS) approach. Then, a qualitative study is carried out to support the quantitative results obtained Findings: Results show that internal and external motives affect internalization, and that the most important issues for internalization are commitment, communication, training, recognition and follow-up. In addition, continuous improvement is key in order to enhance customer results, employee results and social results Originality/value: The contribution of this work is that it provides empirical support to prior research on internalization focused on manufacturing and service organizations, and extends these results to the case of public organizations Abstract : Propósito: Este trabajo analiza la relación entre: a) los motivos para interiorizar un sistema de calidad, b) la interiorización de un sistema de calidad y c) los resultados de clientes, empleados y sociedad en organizaciones públicas, a través de un estudio que replica los análisis previos sobre interiorización realizados en organizaciones manufactureras y de servicios. Diseño/metodología/enfoque: Interiorización de la calidad en organizaciones públicasPara conseguir este objetivo se realiza primero un estudio cuantitativo para comprobar las hipótesis a través de un análisis de ecuaciones estructurales desde el enfoque Partial Least Squares (PLS). Posteriormente se realiza otro estudio cualitativo para apoyar los resultados cuantitativos obtenidos. Resultados: Los resultados muestran que los motivos internos y externos influyen en la interiorización y que los aspectos más importantes para interiorizar un sistema de calidad son la implicación, la comunicación, la formación, el reconocimiento y el seguimiento interno. Además, la mejora continua es clave para mejorar los resultados de clientes, empleados y sociedad. Originalidad/valor: La contribución del trabajo es que proporciona apoyo empírico a los resultados de trabajos previos sobre interiorización centrados en organizaciones manufactureras y de servicios y extiende estos resultados al caso de organizaciones públicas.